Identifying Respondent Group Representation in Extension Capacity Assessments: A Meta-Synthesis of the Literature and a Primary Study - Kevan W Lamm; Alyssa Powell; Alexa Lamm; Kristin E Davis (Journal of International Agricultural and Extension Education, 2022)
A key factor in determining the future of agricultural extension efforts is ensuring that the voices of those who need to be heard are represented at all stages of the decision-making process. As agricultural extension becomes increasingly globalized, it is critical that the diversity of voices represented within capacity assessments likewise increases. Using two distinct approaches, the present study attempts to address a current gap within the extension literature specifically related to extension assessment respondent groups. First, 97 extension related assessment manuscripts were identified during a literature review and analyzed for respondent group. The results indicated most studies included only one respondent group. Among these assessments Clientele and Beneficiaries and Formal Power Roles were the respondent group categories most frequently examined. Next, a primary study was conducted to identify which respondent groups should be represented in capacity assessment according to agricultural extension experts. The panelists had the highest level of agreement regarding the inclusion of extension clientele and beneficiaries within capacity assessments. However, panelists agreed that representation from outside influences and formal power roles were also important to include in the capacity assessment process. The results indicate extension networks should purposively include a diverse set of respondents when conducting assessments to ensure a comprehensive perspective is represented.
Keywords: capacity assessment; extension clientele; extension networks; meta-synthesis